NTT Ikat Woven Cloths: Weaving Tradition, Motifs and their Symbolic Meanings - Siti Rodliyah (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
For most of the East Nusa Tenggara (NTT) people, waving traditions and ikat woven products are not just common local product or cultural manifestations. Each motif in ikat woven product has its own symbolic representation. This is a qualitative descriptive study carried out using an ethnographic research model. The data was collected by observing a number of ikat artisans and their cloth products, providing deep interview to related parties in the manufacturing process including meanings behind the decorative motifs in the ikat woven clothes. This study relies on of data notes linked to the research object as well as images of woven ikat cloth products in NTT.  The result showed that the woven cloth products locally manufactured in NTT, with varied ornamentation and motifs are subject to local knowledge values and symbolic meanings that have a spiritual and mystical aspects. Many motifs on the cloth developed identify each regional area in NTT. Ikat cloth motifs are symbols of communication tools; i.e., Ende-Lio motifs associated with traditional rituals are represented by cloth motifs are the symbols for regulations that must be implemented by the people. For people of North Mollo, NTT, ikat woven product with identical motifs have widely been used for blankets and sarongs named as Pauf designed exclusively for males to wear. In Pauf, there are two interpretations of the rhombus-shaped symbols on Lulat Pohok and Lulat Kollo, which symbolically are the expression or reflection for social interaction between society and the ruler or king.